Pengaruh Literasi Ekonomi dan Kontrol Diri terhadap Perilaku Pembelian Impulsif Mahasiswa Pendidikan Ekonomi Universitas HKBP Nommensen Medan - Halawa, Yusni; Elisabeth Margareta; Manullang, Dapot Tua (Indo-MathEdu Intellectuals Journal, 2024)
This study aims to determine the effect of economic literacy and self-control on the impulsive buying behavior of Economic Education students at HKBP Nommensen University Medan with a population of 64 Economic Education students in 2020 and 2021. The research method used in this study is a quantitative research method. The sampling technique used in this study was the total sampling method. The results of the study showed that economic literacy (X1) partially did not have a negative and significant effect on impulsive buying behavior (Y) with a t count value <t table (-0.125 <1.670). At the same time, the self-control variable (X2) has a partial effect on impulsive buying behavior (Y) with a t count value > t table, namely (5.976 > 1.670). The results of simultaneous testing (F test) showed that there was an influence between economic literacy (X1) and self-control (X2) on impulsive buying behavior (Y). This can be seen from the F count value > F table (30.174 > 2.76). It can be concluded that economic literacy and self-control have an impact on the tendency of impulsive buying behavior. In other words, if the level of understanding of economic literacy and self-control possessed by students increases, it tends to reduce impulsive buying behavior